2003
DOI: 10.1080/01926230309784
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Significance of Metallothioneins in Murine Organs and Tissues Following Mercury Vapour Exposure

Abstract: The fate of inspired mercury vapour (Hg0) is critical in the central nervous system (CNS) where it can circumvent the blood-brain barrier (BBB) at the neuromuscular junction (NMJ) and accumulate indefinitely in motor neurons by retrograde transport. The detoxification of systemic Hg0 by lung and liver requires investigation. We exposed 129/Sv wild-type (Wt) and 129/Sv MT-I, II double knockout (KO) mice to 500 microg Hg0/m3 for 4 hours to investigate the expression of MT in the lung, liver, and spinal cord foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 22 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…In MT-I, II KO mice, the absence of MT-II may therefore affect the radial growth of myelinated axons during development. Recently immunohistochemical studies of MT-I, II showed that its distribution is also found in Schwann cells surrounding the axons in the PNS (Stankovic et al, 2003). Expression of MT-III is however predominantly intra-neuronal at transcription level (Hidalgo et al, 2001), however some reports purport to have detected the protein in astrocytes (Carrasco et al, 1999) although therefore up-regulation in these cells is not possible.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In MT-I, II KO mice, the absence of MT-II may therefore affect the radial growth of myelinated axons during development. Recently immunohistochemical studies of MT-I, II showed that its distribution is also found in Schwann cells surrounding the axons in the PNS (Stankovic et al, 2003). Expression of MT-III is however predominantly intra-neuronal at transcription level (Hidalgo et al, 2001), however some reports purport to have detected the protein in astrocytes (Carrasco et al, 1999) although therefore up-regulation in these cells is not possible.…”
Section: Discussionmentioning
confidence: 97%
“…Immunohistochemical studies have shown that expression of MT-I and II in the CNS of mice is primarily restricted to glial cells such as astrocytes (Young et al, 1991;Nishimura et al, 1992) and that motor neurons do not express this protein. Also, in the PNS, MT-I and II were not detected in the axons of the ventral roots of the spinal cord but were found in the myelin sheath surrounding these axons (Stankovic et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the wider population, the human peripheral motor system is vulnerable to persistent exposure by Hg 0 arising from stressed surfaces of dental amalgam during mastication (Svare et al, 1981;Abraham et al, 1984;Vimy and Lorscheider, 1985;Patterson et al, 1985). Although uptake of metallic mercury by motor neurons is known to occur, it proteins such as metallothionein are not expressed in motor neuron axons (Stankovic et al, 2003). As they are the major constituents involved in cytoskeletal support, NFs largely determine axon calibre (Muma and Hoffman, 1993;Parhad et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, methods simulating conditions of a similar environmental exposure to that attained with the degassing of Hg 0 from dental amalgam have been reported (Stankovic et al, 2003). In this model, a series of perspex chambers beginning with a liquid mercury reaction chamber are used to expose mice to regulated doses of mercury vapor.…”
Section: Introductionmentioning
confidence: 99%
“…The exact role of placental MTs in maternal to fetal transfer of toxic metals including mercury is yet to be elucidated. Recently, MT gene knockout mice (MT-null mice) that do not express MT-I and MT-II genes have been established (Michalska and Choo, 1993;Masters et al, 1994), and the mice are used for the study of the function of MT (Stankovic et al, 2003). The purpose of this study was to examine the localization of both exposed mercury and MTs (MT-I, -II, and -III) following exposure to mercury vapor in the placenta using MT-null and wild-type mice.…”
Section: Introductionmentioning
confidence: 99%